Flavoring agents present in a dentifrice can modify volatile sulphur compounds (VSCs) formation in morning bad breath - Daiane Cristina Peruzzo; Sérgio Luis Salvador; Antonio Wilson Sallum; Getúlio da Rocha Nogueira-Filho (Sociedade Brasileira de Pesquisa Odontológica, 2008)
This study aimed to evaluate the effects of a flavor-containing dentifrice on the formation of volatile sulphur compounds (VSCs) in morning bad breath. A two-step, blinded, crossover, randomized study was carried out in 50 dental students with a healthy periodontium divided into two experimental groups: flavor-containing dentifrice (test) and non-flavor-containing dentifrice (control). The volunteers received the designated dentifrice and a new toothbrush for a 3 X/day brushing regimen for 2 periods of 30 days. A seven-day washout interval was used between the periods. The assessed parameters were: plaque index (PI), gingival index (GI), organoleptic breath scores (ORG), VSC levels (as measured by a portable sulphide monitor) before (H1) and after (H2) cleaning of the tongue, tongue coating (TC) wet weight and BANA test from TC samples. The intra-group analysis showed a decrease in ORG, from 3 to 2, after 30 days for the test group (p < 0.05). The inter-group analysis showed lower values in ORG, H1 and H2 for the test group (p < 0.05). There was no difference between the amount of TC between groups and the presence of flavor also did not interfere in the BANA results between groups (p > 0.05). These findings suggest that a flavor-containing dentifrice seems to prevent VSCs formation in morning bad breath regardless of the amount of TC in periodontally healthy subjects.